(untitled) (Acta Scientiarum. Animal Sciences, 2025)
The determination of optimal crude protein levels in fish diets is crucial due to its essential role in growth and its high cost. This study evaluated the effect of crude protein levels in the diet of piau corró Leporinus lacustris on growth performance, as well as the maximum technical and economic efficiency of this species. Juveniles of L. lacustris were distributed in 20 tanks, 20 L volume, density of six fish, and fed three times daily with 7% biomass. The design was completely randomized with four levels of crude protein (CP): 30, 34, 38, and 42%, and five replicates each. After 60 days of cultivation, the Fulton’s condition factor showed significant differences among treatments, fitting a quadratic regression model. Fish fed diets containing 34% CP exhibited better nutritional status. In contrast, the protein efficiency ratio (PER) followed a decreasing linear trend, with the best performance observed in fish fed 30% CP. Therefore, the diet with 30% crude protein can be recommended for L. lacustris juveniles at this stage of cultivation, as it is close to the optimal level for maximizing the species’ technical and economic efficiency.